The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1037/a0038800
|View full text |Cite
|
Sign up to set email alerts
|

Infant risk factors associated with internalizing, externalizing, and co-occurring behavior problems in young children.

Abstract: The purpose of the current study was to examine the unique and interactive contributions of infant negative emotionality and family risk factors in the development of internalizing-only, externalizing-only, and co-occurring behavior problems in early childhood. The sample included 412 infants and their primary caregivers. Interviews and temperament assessments took place when infants were 5-7 months old, and primary caregivers completed child behavior ratings at ages 2 1/2 and 5 years. Mixed-effects multinomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 54 publications
4
60
0
Order By: Relevance
“…Inadequate parental reflective functioning (RF) and negative parenting behavior (i.e., unresponsiveness, intrusiveness, lack of positive involvement, and hostile or coercive parenting) both have been linked to children’s behavioral problems, whereas adequate parental RF and positive parenting behavior (i.e., sensitivity, involvement, and warmth) have been shown to be a protective factor in this respect (Benbassat and Priel 2012; Edwards and Hans 2015; Ha et al 2011). Therefore, this study investigated whether maternal prenatal RF can predict the development of infant physical aggression and whether maternal sensitivity (i.e., capacity to respond to children’s signals in a contingent, timely and appropriate manner) and intrusiveness (i.e., degree to which parents interfere with their child’s needs and behaviors and handle the child forcefully) mediated or moderated this association.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate parental reflective functioning (RF) and negative parenting behavior (i.e., unresponsiveness, intrusiveness, lack of positive involvement, and hostile or coercive parenting) both have been linked to children’s behavioral problems, whereas adequate parental RF and positive parenting behavior (i.e., sensitivity, involvement, and warmth) have been shown to be a protective factor in this respect (Benbassat and Priel 2012; Edwards and Hans 2015; Ha et al 2011). Therefore, this study investigated whether maternal prenatal RF can predict the development of infant physical aggression and whether maternal sensitivity (i.e., capacity to respond to children’s signals in a contingent, timely and appropriate manner) and intrusiveness (i.e., degree to which parents interfere with their child’s needs and behaviors and handle the child forcefully) mediated or moderated this association.…”
mentioning
confidence: 99%
“…Inadequate and unresponsive parenting behaviors (e.g., ignoring child or spanking child with hand when misbehaving) have been related to children’s behavioral problems (Edwards and Hans 2015; Healy et al 2013; Hughes and Ensor 2006; Keren and Tyano 2012). In contrast, children who have more productive encounters (i.e., more opportunities to engage in activities that are meaningful, challenging, and afford possibilities for learning) are reported to have fewer behavior problems (Benbassat and Priel 2012; Bradley and Corwyn 2005).…”
mentioning
confidence: 99%
“…Thus, results indicate that maternal depressive symptoms, maternal unresponsiveness, and maternal negative behaviors are not linked with pure externalizing symptoms. Importantly, not much is known about the etiology of co-occurring internalizing and externalizing behaviors (Edwards, & Hans, 2015). In future research, it may be useful to consider a person-oriented approach and identify children with consistently low symptoms, those with elevated internalizing only, elevated externalizing only, and comorbid symptoms to determine if each profile or class has unique predictors.…”
Section: Discussionmentioning
confidence: 99%
“…The known familial risk factors range from economic scarcity (Duncan, Magnuson, & VotrubaDrzal, 2014;Huston & Bentley, 2010;Thompson, 2014) to mental health problems (Leight, Fitelson, Weston, & Wisner, 2010;Murray & Cooper, 1997) and attitudes (Velders et al, 2011;Wille, Bettge, & Ravens-Sieberer, 2008) from side of the parents, but also include infant characteristics requiring intensified parental care, such as multiple pregnancies, preterm birth, or illness (Leonard & Denton, 2006). Many studies have shown possible middle-and long-term influences of risk factors on infant health leading to increased mental health problems (Ordonez & Collins, 2015;Rolim Lima et al, 2013;Zalsman, Birmaher, & Brent, 2006) as well as emotional and behavioural problems (Edwards & Hans, 2015;Magee & Roy, 2008;Smeekens, Riksen-Walraven, & van Bakel, 2007;Velders et al, 2011). Moreover, it has been shown that the healthy development of a child is particularly at risk, if several psychosocial risk factors occur simultaneously in the family (Bauman, Silver, & Stein, 2006;Edwards & Hans, 2015;Wille et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown possible middle-and long-term influences of risk factors on infant health leading to increased mental health problems (Ordonez & Collins, 2015;Rolim Lima et al, 2013;Zalsman, Birmaher, & Brent, 2006) as well as emotional and behavioural problems (Edwards & Hans, 2015;Magee & Roy, 2008;Smeekens, Riksen-Walraven, & van Bakel, 2007;Velders et al, 2011). Moreover, it has been shown that the healthy development of a child is particularly at risk, if several psychosocial risk factors occur simultaneously in the family (Bauman, Silver, & Stein, 2006;Edwards & Hans, 2015;Wille et al, 2008). Families in difficult circumstances need special care to strengthen their parental resources.…”
Section: Introductionmentioning
confidence: 99%